Le travail : histoire, perspectives - Dereymez, Jean-William (Grenoble : Presses Universitaires de Grenoble, 1995)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: 19e eeuw; 20e eeuw; arbeid; Frankrijk